1972
DOI: 10.1104/pp.49.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Anion Absorption by Etiolated Wheat Leaves after Vacuum Infiltration

Abstract: Chloride and phosphate uptake by leaf segments of green and etiolated 7-day-old seedlings of Triticum aestivum L. cultivar Capelle is enhanced by light. In the range from 1.0 to 10 millimolar KCl, maximal rates of uptake were obtained with 1.5-millimeter segments. Above 1.5 millimeters, ion diffusion through the cut edge was the rate-limiting factor, uptake being proportional to the amount of cut edge, but vacuum infiltration of the tissue overcame this limitation, allowing uptake to be independent of segment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The fact that vacuum infiltration was required for uptake to be linear with time suggests that the uptake and hence presumably esterification of phosphate are not due primarily to the peripheral cells of the discs. This agrees with recent findings (17) using wheat leaf segments.…”
Section: Discussionsupporting
confidence: 94%
“…The fact that vacuum infiltration was required for uptake to be linear with time suggests that the uptake and hence presumably esterification of phosphate are not due primarily to the peripheral cells of the discs. This agrees with recent findings (17) using wheat leaf segments.…”
Section: Discussionsupporting
confidence: 94%
“…In a previous study of anion absorption by etiolated wheat tissue (10) we reported a marked stimulation of Cl-and PO.' uptake in the light, notably with tissue which had been subjected to vacuum infiltration as a convenient method of obviating cuticular resistance to ion penetration in foliar absorption studies (17).…”
mentioning
confidence: 77%
“…Apart from some minor differences the methods used were those previously reported (10). Seeds of wheat, Triticum aestivum L., cultivar Capelle, were grown for 7 days in darkness in damp horticultural peat and then greened for 2 days prior to use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless specifically stated (as in Table I), chopped tissue was not vacuum infiltrated. Chloride uptake was followed from 5 mm K36Cl (pH 5.5) at 25 C over 24 hr in the dark and in the light (14,500 lux at flask level) as previously reported (10,11). Over this time uptake is linear with whole tissue but with chopped tissue it tends to become hyperbolic (11).…”
Section: Methodsmentioning
confidence: 92%